Christmas on 4th Street : a fool's gold romance - Mallery, Susan (Mallery, Susan. Fool's gold., 2013)
After Nicole Perkins opens her store, The Christmas Attic, in Fool's Gold, California, business is booming; and, as a bonus, gorgeous army doctor Gabriel Boylan has offered to help out during the holiday rush.